Study of various DIP Techniques used for Brain Tumor detection and tumor area calculation using MRI images - Vipin Y, Borole; Seema S, Kawathekar (International Journal of Computer Sciences and Engineering, 2025)
This paper is focused on a study of various techniques of brain tumor detection of MRI images using DIP techniques. The study of various techniques is useful for successful diagnosis and treatment planning of brain tumor. Magnetic Resonance Imaging (MRI) method is used for brain imaging and analyzing internal structures in detail. The accuracy of detecting the brain tumor location and size with good quality takes the most important role of detecting the brain tumor. The brain tumor segmentation carried manually from MRI images is very crucial and time consuming task. Therefore, to avoid that, it needs to use computer aided method for detection of brain tumor. The brain MRI images using various image processing methods like preprocessing, segmentation, morphological operation are used; based on different feature combinations as color (intensity), edge, texture and calculated the tumor area as well as measure the quality of input then output images, it gives a satisfactory result. This research work is helpful in the medical field to detect brain tumors and suggest a treatment plan to the patient